VISUAL AND LINGUISTIC REPRESENTATIONS AND CULTURAL MEANINGS OF BALI IN REDNOTE VIDEOS BY BI LU SI BRUCE (2025) - Yang, Yang; Elfira, Mina (International Review of Humanities Studies, 2026)
This study examines the media presentation of Bali on the Rednote platform, and explores how content creators can build Bali into an idealized tropical lifestyle space. The research selects four videos related to Bali produced by Rednote content creator Bi Lu Si Bruce (Hong Kong House Tour Original as the object of analysis, and uses qualitative research methods combined with semiotic analysis to investigate Cultural symbols conveyed in video visual images and language narratives. The research draws on Hall’s (1997) Cultural Representation theory, Urry’s (1990) Tourist Gaze theory, MacCannell’s (1976) Staged Authenticity theory, and Lefebvre’s (1991) theory of the production of space analyze how meaning is generated through images, discourse and emotional interaction, and also integrate the concept of emotional consistency of Peltari (2022) to explain how audience comments participate in the reproduction of Balinese images. The findings indicate that, through diverse cultural symbols, these videos represent Bali as an idealized Other, a tropical space closely connected to nature, and a site of comfortable residential living, which is further reinforced through affective identification in the comment sections, generating cultural meanings associated with naturalness, relaxation, and healing.